PHYSIOLOGICAL ADAPTATION ASSOCIATED WITH TRANSFER OF MICROBIOTA FROM EXERCISE-TRAINED MICE INTO GERM-FREE MICE - Saddler, Nelson (My University, 2018)
Exercise is known to induce changes in the gut, typically referred to as the ‘forgotten organ’, and changes in gut microbiota can also occur with exercise possibly imparting systemic benefits. The question remains whether or not microbiota from an exercised animal can independently affect skeletal muscle morphology. Our first objective was to examine whether an endurance exercise program could modify the microbiota in donor mice. Second, we aimed to elucidate if such an endurance-trained microbiota could be transferred to germ-free mice via fecal inoculation. Finally, we sought to determine how the morphology and functional characteristics of skeletal muscle were influenced as a result of fecal inoculation. We hypothesized that germ-free mice recipients inoculated with the microbiota from endurance trained donors would undergo morphological changes in muscle fibre type composition and physiological changes in skeletal muscle function associated with a more oxidative phenotype. Eight-week-old male C57BL/6NCrl donor mice (n = 20) were randomized into two groups: one group completed an endurance exercise training protocol on a treadmill machine 3x/week for 11 weeks (n = 10) while one group remained cage-bound (n = 10). Ten-week-old male (n = 7) and female (n = 9) germ-free mice were colonized with the cecal microbiota of the donor mice in that, equal numbers of germ-free mice were inoculated with exercised-microbiota as sedentary-microbiota. Glucose metabolism and performance measures were evaluated in the donors as well as the recipients post-inoculation. Muscle tissue was extracted for immunohistochemistry and mitochondrial assays. During the intra-peritoneal glucose tolerance test (IPGTT), significant differences in blood glucose were found at 30min between exercise-inoculated and sedentary-inoculated (23.4 ± 2.2; 29.0 ± 1.9 mmol/L, p<0.05).and change in blood glucose relative to baseline (12.04 ± 2.4; 18.3 ± 1.9 mmol/L, p<0.01). There were significant sex-based differences in the blood glucose response in inoculated animals such that there were significant differences in blood glucose between the exercise-inoculated females and sedentary-inoculated females at 15mins (28.4 ± 2.4; 30.6 ± 1.1 mmol/L, p<0.05) and 30mins (24.7 ± 3.6; 29.9 ± 2.4 mmol/L, p<0.01), however no differences between exercise-inoculated males and sedentary-inoculated males. In addition, there were significant differences in the change in blood glucose relative to baseline between the exercise-inoculated females and sedentary-inoculated females at 15mins (12.3 ± 1.9; 20.6 ± 0.8 mmol/L, p<0.01) and 30mins (10.2 ± 2.6; 19.9 ± 2.1 mmol/L, p<0.001). This novel characterization of a link between gut microbiota and skeletal muscle suggests a transmissible capacity of microbiota to impart properties of ‘healthy’ muscle into compromised populations.
Keywords: gut bacteria; germ-free; microbiota; endurance exercise; gnotobiotic; inoculation